Empirical seismic site effect analysis for the city of Tehran using H / V and methods. Issue 4 (18th May 2020) - Behrou, Reza; Haghpanah, Fardad; Foroughi, Hamid
Abstract: This paper presents empirical seismic site effect analysis for Tehran city, the capital of Iran. Empirical methods using both spectral ratio of the horizontal components of sedimentary site to rocky site ( H s / H r ) (site/reference) and horizontal to vertical spectral ratio ( H  /  V ) are considered. To estimate the seismic site effect parameters using the empirical methods, recorded motions from Firozabad-Kojour (2004) and Kahak-Qom (2007) earthquakes are analysed. The recorded motions in rocky stations are used for the H s / H r method. Site amplification ratios in various frequency ranges are extracted from the results of both H s / H r and H  /  V methods. The peak surface accelerations are computed using the site amplification ratios, for different frequency ranges, and compared with the recorded peak accelerations. Based on the values of the least square relative errors, the results from the H s / H r method for the 1–10 Hz frequency range show a good agreement between the calculated and recorded peak surface accelerations, and thus, this frequency range can be considered a reliable range for the results of this study to be used for seismic design purposes in the study area.